Avoidance of phenylthiocarbamide in mature Targhee and Rambouillet rams. Issue 4 (5th October 2019) - Henslee, Dillan; Yelich, Joel; Taylor, J Bret; Ellison, Melinda
Abstract: Shrub encroachment on grasslands is a worldwide issue and sheep are a potential tool for mitigating shrub encroachment. Many shrubs, however, contain bitter-tasting compounds that may deter grazers. Cattle and sheep commonly graze rangelands, but of the two, sheep have a greater tolerance for bitter compounds and would be expected to consume more bitter-tasting vegetation. We hypothesized that sheep could detect (i.e., taste) bitter-tasting compounds and the sensitivity to these compounds would vary from animal to animal. The objective of this study was to determine whether sheep could detect the bitter-tasting compound phenylthiocarbamide (PTC), and if so, what PTC concentration would elicit an avoidance response. Using a crossover study design, mature Rambouillet and Targhee rams ( n = 30) were subjected in randomized order to various PTC concentrations mixed in the drinking water (PTC solution). In trials 1 and 2 ( n = 15/trial), 0.20, 0.56, 1.57, 4.39, and 12.29 mM and 0.20, 0.43, 0.94, 2.03, and 4.39 mM of PTC were tested, respectively. On test days, PTC solution (trial 1: 1.5 kg; trial 2: 3.0 kg) and water (same amounts) were offered for ad libitum intake in a side-by-side presentation for 1 h in trial 1 and 2 h in trial 2. Each test day was followed by a rest day where PTC solution was replaced with water to limit potential carry over effects into the next test day. Consumption of PTC solution for each PTC concentration was expressed as the percentage of PTC solution intake of total morning fluid intake. There was no effect ( P > 0.74) of sequence that rams received PTC solutions on PTC consumption during either trial. As PTC concentration increased, percentage of PTC solution intake decreased ( P ≤ 0.01) for both trials. The greatest decrease in percentage of PTC solution intake occurred between 1.57 and 4.39 mM (58%) for trial 1 and 2.03 and 4.39 mM (72%) for trial 2. In trial 2, the least percentage of PTC solution intake was the 4.39 mM PTC concentration, which was different ( P ≤ 0.05) from lesser PTC concentrations. All other PTC concentrations did not differ ( P > 0.05) from each other in percentage intake. This research suggests rams could taste the PTC, and the concentration at which PTC solution was avoided varied across rams. It may be possible to select sheep, based on demonstrated avoidance of PTC, for targeted grazing applications to manipulate vegetation toward range management goals.